The Fabric of Transnational Political Activism: “Révolution Afrique” and West African Radical Militants in France in the 1970s - (:unkn) unknown (My University, 2018)
This article locates itself at the intersection of the social history of postcolonial migrations and the intellectual history of leftism and Third-Worldism in the aftermath of May ’68. It is the first study of the radical political group Révolution Afrique. From 1972 until its ban by the French government in 1977, this organization forged by African and French activists mobilized against neocolonial ideologies and policies on both sides of the Mediterranean. By tracing the rise and fall of the organization through extensive archival research and in-depth interviews, the article explores the changing meanings of transnational activism by weaving together the biographical paths of the activists, the institutional and political constraints they faced, and the ideological framework within which they operated. During this short time frame, the transnational agenda that made sense among African workers and students in the early 1970s became irrelevant. The increasing repression of political dissent in Africa and France, the suspension of migratory flows, and the French government’s implementation of return policies in the late 1970s forced the group’s African activists to adopt a more national approach to their actions, or simply withdraw from high-risk activism. Despite the dissolution of Révolution Afrique, this collective endeavor appears to have been a unique experience of political education for African activists, transcending distinct social and national boundaries that until now have been left unexamined by social scientists specialized in the complex history of the relationships between France and Africa.
Keywords: African Research